Role of Ubiquitin-Mediated Degradation System in Plant Biology - Sharma, Bhaskar; Joshi, Deepti; Yadav, Pawan K.; Gupta, Aditya K.; Bhatt, Tarun K. (Frontiers in Plant Science, 2016)
Ubiquitin-mediated proteasomal degradation is an important mechanism to control protein load in the cell. Ubiquitin binds to a protein on lysine residue and degrades the protein via 26S proteasome system. The abnormal proteins, regulators of many processes are targeted for degradation by Ubiquitin proteasome system. It allows cells to maintain the response to cellular level signals and altered environmental conditions. The ubiquitin-mediated proteasomal degradation system plays a greater role in the plant biology, including abiotic stress, immunity and hormonal signaling by interfering in key components of these pathways. The involvement of ubiquitin system in many vital processes led scientists to explore more about the ubiquitin machinery and most importantly its target. In this review, we have summarized recent discoveries of the plant ubiquitin system and its involvement in critical processes of plant biology.